2020
DOI: 10.1007/s00432-020-03191-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of GoFundMe® to crowdfund complementary and alternative medicine treatments for cancer

Abstract: Purpose Complementary and alternative medicine (CAM) use is common amongst cancer patients. However, there is growing concern about its safety and efficacy. Online crowdfunding campaigns represent a unique avenue to understand the cancer patient's perspective for using CAM or declining conventional cancer therapy (CCT). Methods Five hundred GoFundMe campaigns from 2012 to 2019 detailing financial need for cancer treatment were randomly selected and reviewed for endorsement of CAM use, reasons for using CAM, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 24 publications
1
41
1
Order By: Relevance
“…The types of CAM most frequently used by patients in our study were natural products, herbs, vitamin C and other vitamins, dietary supplements and microelements. The same therapies have commonly been reported by other authors [17,[24][25][26][28][29][30][31][32][33]; however, there are some therapy preferences that have been reported to be nation-specific. In the USA, the most popular CAM were vitamins, minerals, herbal supplements and green tea [28,29].…”
Section: Types Of Camsupporting
confidence: 65%
See 1 more Smart Citation
“…The types of CAM most frequently used by patients in our study were natural products, herbs, vitamin C and other vitamins, dietary supplements and microelements. The same therapies have commonly been reported by other authors [17,[24][25][26][28][29][30][31][32][33]; however, there are some therapy preferences that have been reported to be nation-specific. In the USA, the most popular CAM were vitamins, minerals, herbal supplements and green tea [28,29].…”
Section: Types Of Camsupporting
confidence: 65%
“…Being female, of a younger age and highly educated predicted CAM use in other populations [16,20,22,[24][25][26][27][28][29][30][31]. Additionally, CAM users were more likely to have advanced stages of cancer (IV) and have a history of delayed diagnosis [32]. CAM were more likely to be used by breast cancer and lung cancer patients [24].…”
Section: Predictors Of Cam Usagementioning
confidence: 99%
“… 24 , 25 , 26 However, when compared with more prevalent cancers such as breast, colon and lung, patients with kidney cancer less commonly sought funds for complementary and alternative medicine‐ this was echoed by our results. 26 Instead, patients chiefly called for treatment‐related financial assistance for more widely‐accepted therapies such as nephrectomy, radiotherapy, and chemotherapy. 27 Finally, when compared with Cohen et al’s multiorgan cancer cohort, it may be notable to mention that a higher proportion of kidney cancer patients reported themselves as the primary wage earner and had subsequent loss of job/reduction of hours due to illness.…”
Section: Discussionmentioning
confidence: 55%
“…Additional research has found that patients also crowdfund in order to cover costs of experimental and “scientifically unsupported” treatments to achieve therapeutic success and pain reduction 24–26 . However, when compared with more prevalent cancers such as breast, colon and lung, patients with kidney cancer less commonly sought funds for complementary and alternative medicine‐ this was echoed by our results 26 . Instead, patients chiefly called for treatment‐related financial assistance for more widely‐accepted therapies such as nephrectomy, radiotherapy, and chemotherapy 27 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation